Geological Investigation and Treatment of the Cabean Dam Foundation - Muhammad Perwira Rachman; Sri Sangkawati; Ignatius Sriyana; Yudi Kurniawan (Journal La Multiapp, 2026)
Embankment dams are critical infrastructure requiring comprehensive geological and geotechnical investigation to ensure long-term structural integrity and prevent catastrophic failure. This study presents the results of two-stage Multichannel Analysis of Surface Waves (MASW) investigations conducted at Cabean Dam core zone to characterize shear wave velocity (Vs) profiles and identify weak zones susceptible to seepage and slope instability. The first stage (2022) involved 17 survey lines while the second stage (2025) comprised 11 additional lines targeting critical areas. Shear wave velocity values ranged from 78–756 m/s, indicating significant material heterogeneity. Low Vs anomalies (78–200 m/s) were identified in the upper 0–7 meter depth at survey lines L-01, L-07, L-08, and L-09, correlating with residual soil having high permeability values up to 3.06×10⁻⁴ m/s and Lugeon values reaching 25.34 Lu. Integration of MASW data with borehole logs confirmed material classifications ranging from Site Class E (soft soil) at shallow depths to Site Class B (stiff soil) at greater depths. The identified weak zones pose significant risks for seepage, internal erosion (piping), and slope instability, requiring remedial measures including recompaction, optimized internal drainage design, and enhanced instrumentation monitoring. This research contributes methodological advancement in applying MASW as an integral component of staged investigation protocols for embankment dam projects, particularly for monitoring and refining geological-geotechnical conditions during construction phase. Results serve as a reference for practitioners and researchers in geotechnical dam engineering for improving safety and reliability of embankment dam infrastructure in Indonesia.